The effects of using the instructional systems design process on transfer of training : a developmental study in Malaysia - Malekzadeh, Robabeh; Ismail, Maimunah; Ahmad, Aminah (2011)
This study investigated the effects of using the "Instructional Systems Design" (ISD) process on transfer of training achievement. Two groups of employees were trained. The experimental group was given a structured training program using the ISD process in terms of ADDIE modelthrough the researcher while the control group received the conventional training by the training department. The two groups were assessed five months after the period of training. Results of the assessment showed a significant difference between the two groups. The experimental group assessed its transfer of training achievement better than the control group. However, the immediate supervisors of these two groups assessed the training transfer achievement for both of them in the similar degree. The study offers systematic and instructional-basedoperational guidelines for measuring transfer of training in organizational setting.